O Sistema de Vigilância Alimentar e Nutricional como instrumento de monitoramento da Estratégia Nacional para Alimentação Complementar Saudável - Carolina Souza Ferreira (2013)
It is recommended by the Ministry of Health that the Food and Nutritional Surveillance System (Sistema de Vigilância Alimentar e Nutricional - Sisvan) indicators for children under 2 years old are used to monitor the National Strategy for Complementary Healthy Feeding (Estratégia Nacional para Alimentação Complementar Saudável - Enpacs). The Sisvan aims to generate information about the food and nutritional situation of the population. The Enpacs contains the guidelines to be adopted to reinforce, within primary care, the actions to promote complementary healthy feeding. Objective: To analyze the Sisvan as a tool for Enpacs monitoring in the 40 cities of the Belo Horizontes Regional Health Superintendence (SRS-BH). Methods: A descriptive study involving all children under 2 years old who were assisted by Sisvan Web in the years 2008 to 2011 was conducted. The coverage of Sisvan Web was calculated by dividing the number of children under 2 years old assisted by Sisvan Web by the population in the same age group. The medians coverages for four municipalities groups were checked, they were established according to population size. The results of the children monitored monthly by the Sisvan Webs anthropometric index weight/age were compared with the numbers of children weighed in the same period according to the Primary Care Data System (Siab). A survey was sent to the Sisvans technical references of the evaluated cities to gather information on the Sisvans action. Results: The coverage of the Sisvan Web in all cities ranged from 4.3% (in 2008) to 10.7% (in 2011). The coverages medians of the evaluated groups tended to increase with time (p = 0,003). Although the group of cities classified as large city has presented lower medians than the other groups, the difference among groups was not significant (p = 0,057). For all the months the number of children weighed according to Siab was greater than the number of children assisted by Sisvan Web concerning the weight/age index. The survey was answered by 38 cities of the SRS-BH, and out of these, 31.6% have reported using data from Sisvan Web to establish nutritional intervention actions. Final considerations: The study has identified low coverage, poor utilization of data and the necessity to reinforce the Sisvan to generate consistent information about the food and nutritional situation of children under 2 years old, becoming, thus, suitable for Enpacs monitoring.